THE EFFECT OF RAMADI SEWAGE TREATMENT PLANT ON THE PHYTOPLANKTON AND SOME PHYSICO – CHEMICAL CHARACTERS IN EUPHRATES RIVER , IRAQ (Baghdad Science Journal, 2025)
Four localities were selected in Euphrates River and Ramadi sewage treatment plant to collect water samples monthly during the period between October 2001 to July 2002 . Total cell count of phytoplankton and its physico- chemical concentrations were determined . The study aimed to demonstrate the effect of Ramadi sewage treatment plant on Euhprates River . It is concluded that the sewage had an dilution effect for the total hardness , total alkalinity , electrical conductivity and salinity of Euphrates River , but it is also caused in the presence of a contaminated area . This was cleared from the depletion of dissolved oxygen and high values of biological oxygen demand with lower valuse of pH in this area . The water of Euphrates River may classified as a hard water with high concentration of Ca and Mg. Bacillariophyceae(Diatoms) was dominated followed by chlorophyceae and cyanophyceae. The other classes were very spare and did not affect the total cell counts .